2012
DOI: 10.1039/c2pp05417e
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based photodynamic therapy

Abstract: We have transfected murine neural stem cells (NSCs) with a plasmid expressing Gaussia luciferase (gLuc). The enzyme is secreted from the cells. We have used the gLuc-containing supernatant from cultured NSCs to perform in vitro photodynamic therapy of murine melanoma cells (B16F10). The treatment system was comprised of 5-aminolevulinic acid as a prodrug for the synthesis of the 10 photosensitizer protoporphyrin IX, Gaussia luciferase, and its substrate, coelenterazine. A significant reduction in the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…21 Therefore, cell-mediated transport of anticancer drugs into the tumor tissue is, in the opinion of the authors, the most viable strategy to develop intelligent alternatives to chemotherapy. 10,[22][23][24][25][26][27] Transport cells have the ability to migrate to tumors and metastases following cytokine/chemokine gradients. 28 Among them are stem cells, 29 monocytes/macrophages 30,31 and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, cell-mediated transport of anticancer drugs into the tumor tissue is, in the opinion of the authors, the most viable strategy to develop intelligent alternatives to chemotherapy. 10,[22][23][24][25][26][27] Transport cells have the ability to migrate to tumors and metastases following cytokine/chemokine gradients. 28 Among them are stem cells, 29 monocytes/macrophages 30,31 and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…28 Among them are stem cells, 29 monocytes/macrophages 30,31 and neutrophils. 32,33 Neural stem cells, which can be, principally, cultured and matched to patient-types, have been successfully utilized for cell-mediated therapies in rodent models, 22,27,34 as well as neutrophils 35,36 and monocytes. 10,23,24,27 The use of autologous cells has the potential of developing truly patient specic therapies, and also of signicantly lowering the regulatory barriers for cell-based human cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…cells exposed to high artificial UV-B doses. Both processes represent a tremendous advantage for survival in extreme natural ecosystems such as the High Altitude Andean Lakes as they allow cells to anticipate daily UV fluctuations and, in turn, protect the integrity of cell structure (Albarracín et al, 2012;Portero et al, 2019;Thattai & Van Oudenaarden, 2004;.…”
Section: Discussionmentioning
confidence: 99%
“…In the Central Andean region in South America, high-altitude ecosystems (3500-6000 m asl) are distributed across Argentina, Chile, Bolivia and Peru, in which poly-extremophilic microbes thrive under extreme environmental conditions (Albarracín et al, 2009;Albarracín, Gärtner, et al, 2016;Farías, 2020;Orellana et al, 2018;Vignale et al, 2021). Previous works proved the high tolerance profiles of these extremophiles to antibiotics, dryness, heavy-metal, arsenic, hypersalinity, and UV irradiation (Albarracín et al, 2009(Albarracín et al, , 2012Alonso-Reyes, Farias, et al, 2020;Belfiore et al, 2013;Dib et al, 2009;Flores et al, 2009;Kurth et al, 2015Kurth et al, , 2017Omar Federico Ordoñez et al, 2018;Orellana et al, 2018;Perez et al, 2020;Pérez et al, 2017a;Portero et al, 2019;Nicolas Rascovan et al, 2015;Rasuk et al, 2017;Saona et al, 2021;Zannier et al, 2019;. Moreover, various underlying mechanisms and cellular processes were identified that indicate how these indigenous microbes cope with these multiple stress conditions, thus presenting an interesting side-aspect of opening avenues of research for novel biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The overall long-term success in vivo was attributed to a combined priming of the tumor microenvironment by PDP enabling high doses of chemotherapeutic agent delivery while cancer and stem cells were both killed agnostically. It should be noted that studies [42,332,333], which evaluated combination therapies on cancer stem cells/cancer cells and PDT have used established cell lines and not patient derived tissues, which makes the significance of these observations ambiguous. The heterogeneity observed in human tumors is lost when generated from single cell lines and therefore the impact on the loss of stem cell markers from tumor is not completely obvious.…”
Section: Targeted Delivery Of Nanomedicines For Photodynamic Therapymentioning
confidence: 99%